Faktor-Faktor yang Memengaruhi Tingkat Kriminalitas di Indonesia Tahun 2018 - Andrian Dwi Putra; Gracilia Stevi Martha; Muhammad Fikram; Risni Julaeni Yuhan (Universitas Sebelas Maret, 2020)
Crime still often occurs easily in daily life in Indonesia. This study aims to determine factors that influence the level of crime in Indonesia in 2018 and the magnitude of the influence of each factor. The data used in this study are secondary data obtained from the Statistics Indonesia (BPS). The method used in this study is path analysis, and the variables used are population, education, unemployment rate, poverty rate, and crime. As a result, population and poverty influenced crime while education influenced poverty significantly.Keywords: crime, path coefficient, path analysis